INVESTIGATION OF TRIBO-TECHNICAL COATING PROPERTIES OBTAINED BY ELECTRO-CONTACT FLASHING - K. E. Beljavin; A. V. Sosnovsky (Наука и техника)
The paper shows results of shock-abrasive wear tests of coatings obtained by electro-contact flashing. Iron- and nickel-base powders and their mixture are used as a filler material. metallographic investigations of the obtained coatings are presented in the paper.